Farmer`s Perception about Resurgence of Brown Planthopper, Nilaparvata Lugens (Stål) in Bangladesh - Uddin, A B M A; Islam, K S; Jahan, M; Ara, A; Afrin, S (Bangladesh Rice Journal, 2020)
Studies were conducted on resurgence of brown planthopper (BPH), Nilaparvata lugens (Stål) and its possible management through a survey in six different regions (viz Tanore, Rajshahi; Niamatpur, Naogaon; Nachole, Chapai Nawabganj; Sadar, Dinajpur; Tarash, Sirajganj and Trishal, Mymensingh). Farmer’s perception of BPH resurgence and its management was more or less similar in different regions with some exception. About 60% farmers were able to identify BPH and 40% farmer could identify the pest problem at the later stage of the infestation when burning symptom was visible in patches. All the respondent farmers (100%) relied on use of insecticide where the selection of insecticide as well as its application was not appropriate. Bangladesh Rice j. 2019, 23(1): 21-33